The Effect of Providing Education on the Use of Inhalers on Asthma Degrees Based on the Asthma Control Test (ACT) in Patients at Tanjungpura Hospital - Bayani, Sri; Tarigan, Amira Permatasari; Pandia, Pandiaman; Amelia, Rina; Jefri, Budi (Journal of Society Medicine, 2024)
Introduction: The main goal of asthma treatment is to control symptoms and reduce emergency department (ED) visits due to acute exacerbations. Drug delivery through inhalation is an important component of asthma management. Patients with asthma should have a good knowledge of their disease to recognize signs of worsening that can be prevented by early detection. Asthma control can be evaluated using the Asthma Control Test (ACT). To determine the effect of providing education on the use of inhalers on the degree of asthma based on the ACT in patients at Tanjungpura Regional General Hospital. Methods: This quasi-experimental study conducted from March 2024 to May 2024, used a one-group pre-test and post-test design to evaluate the effect of education via smartphone applications on asthma control (ACT). Obtained 54 patients who were diagnosed asthma at Tanjungpura Regional General Hospital. The sample consisted of asthma patients using inhalers, selected consecutively based on inclusion and exclusion criteria. Results: Most patients were female (64.8%) with ages 18-60 years (83.3%). The majority were housewives (46.2%). Post-test showed that 75.9% of patients had partial asthma control. All patients (100%) used inhalers correctly after education. There was a significant difference in ACT results before and after education (P-value 0.001) and an increase in ACT scores after the first and second education (P-value 0.002 and 0.001, respectively). Conclusion: Providing education on the use of inhalers has a positive effect on ACT scores in asthma patients, with an increase in the mean ACT score from 15.67 before education to 17.11 after the first education, and 20.96 after the second education.